2022
DOI: 10.3389/fcell.2022.844623
|View full text |Cite
|
Sign up to set email alerts
|

Human Endometrial Organoids: Recent Research Progress and Potential Applications

Abstract: Since traditional two-dimensional (2D) cell culture cannot meet the demand of simulating physiological conditions in vivo, three-dimensional (3D) culture systems have been developed. To date, most of these systems have been applied for the culture of gastrointestinal and neural tissue. As for the female reproductive system, the culture of endometrial and oviductal tissues in Matrigel has also been performed, but there are still some problems that remain unsolved. This review highlights recent progress regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…To our knowledge, R-spondin1 and Noggin were the main factors in maintaining the stemness of the organoids in the culture medium. Complete withdrawal of R-spondin1 and Noggin could reduce the proliferation efficiency of the organoids or enhance apoptosis 23 , 24 . R-spondin1 has been implicated in the activation and regulation of the Wnt signaling pathway 25 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, R-spondin1 and Noggin were the main factors in maintaining the stemness of the organoids in the culture medium. Complete withdrawal of R-spondin1 and Noggin could reduce the proliferation efficiency of the organoids or enhance apoptosis 23 , 24 . R-spondin1 has been implicated in the activation and regulation of the Wnt signaling pathway 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In the 21st century, several laboratories have reported the generation of human endometrial organoids by enzymatically dissociating endometrial tissue, which subsequently matures and grows into hollow spherical structures in specific media [ 28 ]. Compared with endometrial organoids derived from animal models, specific nutrients added into the human endometrial organoid culture system are different, including growth factors, hormones, and key regulators involved in signaling pathways [ 29 ]. These organoids show potent stability in retaining genetic traits during cell division and differentiation, and their ability to restore secretory characteristics under thawing conditions after cryopreservation has been fully tested [ 30 ].…”
Section: Engineering Technologies Focusing On the Endometriummentioning
confidence: 99%
“…Recently, powerful new research models have been established in the form of organoids, shown to be highly instrumental and accurate to study endometrium biology and disease ( 4 6 ); and in detail reviewed in ( 2 , 7 , 8 ). Organoids are 3D cell constructions that in vitro self-develop from (diseased) tissue (stem) cells when embedded in a supporting ECM (hydrogel) scaffold, and cultured in an optimized, well-defined medium, specifically encompassing stem cell- and embryogenesis-regulatory factors ( 9 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%